The Application of the Talqin Jama’ah Method in Increasing the Effectiveness of Students Reading the Qur’an At the Al-Quran Education Park - Nurjannah, Nurjannah; Kartini, Kartini; Makmur, Makmur; Tasbih, Ayu (Educational Journal of Learning Technology, 2025)
This study explores the application of the Talqin Jama’ah method to improve the effectiveness of Qur’an reading learning for 2A grade students at TPA SDN 5 Salamae. Using Classroom Action Research with planning, action, observation, and reflection cycles, the study involved 17 students. Data were collected through observation, tests, and documentation. The results show a significant improvement in students’ Qur’an reading skills and engagement from Cycle I to Cycle II. These findings demonstrate that the Talqin Jama’ah method effectively enhances learning and supports better Qur’an literacy in early learners.